Core-shell Semiconductor Nanocrystals: Effect of Composition, Size, Surface Coatings on their Optical Properties, Toxicity and Pharmacokinetics - T. Al-Jamal, Wafa' (Current Pharmaceutical Design, 2017)
Quantum dots are semiconducting nanocrystals that exhibit extraordinary optical properties. QD have shown higher photostability compared to standard organic dye type probes. Therefore, they have been heavily explored in the biomedical field. This review will discuss the different approaches to synthesis, solubilise and functionalise QD. Their main biomedical applications in imaging and photodynamic therapy will be highlighted. Finally, QD biodistribution profile and in vivo toxicity will be discussed.
Keywords: fluorescence